Towards homeostasis: Correlations in the Gut Microbiome of Young Overweight Females following a Yeast Nutritional Supplement - Joller, Peter; Cabaset, Sophie (Archives of Clinical and Biomedical Research, 2021)
Background: Previous scientific studies showed that the yeast-based dietary supplement affected the gut and the bowel movement significantly. To find reasons concerning this matter we devised this gut microbiome study. Methods: At the beginning and after three weeks of supplementation the stool samples of the 26 female probands were analyzed by shotgun metagenomics sequencing. The results were assessed by multiple statistical methods. The initial percentage of a certain bacterium was compared with the difference at the end of the study using correlation statistics. Results: Sixty-eight gut bacteria were present in all probands in different percentages. The overall difference from day 1 to day 21 in all participants was more than ±20%. The in-depth analysis of these differences revealed a correlation between the initial value and increase or decline at the end in the sense that high values for a certain bacterium recessed and low values expanded in the direction of an average. Conclusions: Within three weeks the yeast-based nutritional supplement influenced the bacteria of the gut microbiome in a tendency towards mean values. This could be due to immunological actions and/or quorum sensing.